2015
DOI: 10.1142/s0217751x1541002x
|View full text |Cite
|
Sign up to set email alerts
|

Review of physics results from the Tevatron: QCD physics

Abstract: We present a summary of results from studies of quantum chromodynamics at the Fermilab Tevatron collider by the CDF and the D0 experiments. These include Run II results for the time period up to the end of Summer 2014. A brief description of Run I resultsis also given. This review covers a wide spectrum of topics, and includes measurements with jet and vector boson final states in the hard (perturbative) energy regime, as well as studies of soft physics such as diffractive and elastic scatterings, underlying a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…The corresponding |uudbb intrinsic bottom heavy-quark Fock state can account for the observation of pp → Λ b X at high x F at the ISR [133]. The presence of charm at high x in the proton structure function is also indicated by the anomalously large pp → γcX rate reported by the D0 experiment at the Tevatron [134,135].…”
Section: Supplemental Materialsmentioning
confidence: 79%
“…The corresponding |uudbb intrinsic bottom heavy-quark Fock state can account for the observation of pp → Λ b X at high x F at the ISR [133]. The presence of charm at high x in the proton structure function is also indicated by the anomalously large pp → γcX rate reported by the D0 experiment at the Tevatron [134,135].…”
Section: Supplemental Materialsmentioning
confidence: 79%
“…replacing the Z boson with a final-state photon, which would permit probing lower values of Q [48][49][50]. Such measurements have been made at the Tevatron [51,52] and are suggestive of IC [53]. The LHCb calorimeter system is not well suited to studying high-energy photons; however, LHCb has demonstrated that it can reconstruct and precisely measure the properties of γ conversions to e + e − [54].…”
Section: Expected Sensitivitymentioning
confidence: 99%
“…These studies have being discussed in the QCD chapter of this review. 50 3.4. Asymmetry Measurements…”
Section: Associated Jet Productionmentioning
confidence: 99%